Undue Hate - Stone, Daniel F. (The MIT Press, 2023)
How to understand the mistakes we make about those on the other side of the political spectrum—and how they drive the affective polarization that is tearing us apart.It's well known that the political divide in the United States—particularly between Democrats and Republicans—has grown to alarming levels in recent decades. Affective polarization—emotional polarization, or the hostility between the parties—has reached an unprecedented fever pitch. In Undue Hate, Daniel F. Stone tackles the biases undergirding affective polarization head-on. Stone explains why we often develop objectively false, and overly negative, beliefs about the other side—causing us to dislike them more than we should.Approaching affective polarization through the lens of behavioral economics, Undue Hate is unique in its use of simple mathematical concepts and models to illustrate how we misjudge those we disagree with, for both political and nonpolitical issues. Stone argues that while our biases may vary, just about all of us unwisely exacerbate conflict at times—managing to make ourselves worse off in the long run. Finally, the book offers both short- and long-term solutions for tempering our bias and limiting its negative consequences—and, just maybe, finding a way back to understanding one another before it is too late.